Kerangka Konsep Model Pengembangan Kurikulum Pendidikan Karakter Melalui PAI Berbasis “Tarbiya Mukmin Ulul Albab” - Lailial Muhtifah; Ricka Tesi Muskania (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2017)
This paper intends to examine the concept of character education curriculum development through PAI-based tarbiya mukmin ulul albab. the approach used in this research is literature study (library research) with literature review method. The results showed that conceptually the development of the curriculum found a theoretical model with the name